Fatores associados ao aleitamento materno em recém-nascidos prematuros em unidade neonatal - Cláudia Gonçalves de Oliveira (2021)
Premature babies are almost certainly hospitalized in a Neonatal Intensive Care Unit, due to the difficulty of adapting to extrauterine life. In this scenario full of technologies and technicalities, guaranteeing breast milk to premature babies is a challenge that is becoming viable. In this sense, through two studies, facilitating factors for the breastfeeding process were investigated, as well as the difficulties encountered by mothers and the Nursing team willing to this practice. The first research aimed to verify the association between training and experience of Nursing professionals in the neonatal area with data on professional practice, referring to breastfeeding. The second study aimed to verify the association between socioeconomic, pregnancy and childbirth characteristics of mothers of premature newborns, data on premature newborns at birth and during hospitalization, speech-language pathology monitoring and Nursing care with the type of diet. to hospital discharge. As for the methods of the first study, it is a descriptive and analytical, cross-sectional study, with a qualiquantitative approach, carried out with 48 Neonatology Nursing professionals, who answered a structured questionnaire on identification, training, experience and performance, in addition to their opinion on factors that facilitate and hinder the breastfeeding of hospitalized premature babies. The second is a descriptive and analytical, cross-sectional study with a qualitative and quantitative approach, carried out with 115 mothers of newborns hospitalized in a neonatal unit, who answered a structured questionnaire on socioeconomic data, pregnancy and opinion on factors that influence sucking. from premature to maternal breast. In addition, data on childbirth and hospitalization of the baby were investigated through the electronic medical record. The association between type of diet and hospital discharge was evaluated using univariate and multivariate analysis. The results were that the participants were female, 83.3% had professional training as a nursing technician and 81.3% had a weekly workload of 30 hours. There was an influence of the work shift and the weekly workload on the frequency of stimulation and facilitation of parents' access to the neonatal unit. There was a relationship between the work shift and the frequency with which they encouraged the newborn to remain in the kangaroo position during hospitalization, between the time since graduation and the frequency with which they advised the parents about this practice after discharge and between position, weekly workload and work shift with the frequency of guidance to parents regarding the practice of breastfeeding, after discharge. In the other study, the independent association between schooling, marital status, previous pregnancies, positive history of breastfeeding, complications at birth, time of start of enteral diet and tube use and number of days of hospitalization with the type of feeding was obtained. to hospital discharge. It was concluded that professional training, education level, position held, weekly workload and work shift influence the professional performance of Nursing in the area of Neonatology. While the second study concluded that mothers who were married or in a stable relationship, with higher education, a history of another pregnancy and having breastfed the other child favored exclusive breastfeeding at discharge, as well as babies who did not suffer complications in the delivery room, used an enteral tube. in less time and were hospitalized for less time.